The Development of a Professional Learning Community Model by Using Lesson Study with Mentoring to Develop Competency in Active Learning Management of Assistant Teachers - Eamtip, Mutita; Sithsungnoen , Chanasith (Dhammathas Academic Journal, 2025)
The purposes of the research were to: 1) investigate the foundational data and needs for developing a professional learning community model and 2) develop and evaluate the quality of the professional learning community model. It is a mixed-methods research. The Population and target groups used in the research was 9 school administrators and 44 assistant teachers. The tools for collecting the data included 1) document analysis forms, 2) interview forms, 3) questionnaires, and 4) model suitability evaluation forms. It is a Index of item objective congruence is 1.00 The data were analyzed using means, standard deviations, and content analysis. The research findings revealed that: 1. The study of foundational data on developing the professional learning community model disclosed that administrators, teachers, and experts emphasized the importance of developing teachers' competencies in active learning through a professional learning community process, combined with lesson study and mentorship. This approach promotes assistant teachers' knowledge and understanding of active learning, learning design, and learning management, ultimately leading to improved student outcomes. 2. The professional learning community model, 2S2L Model, consists of 6 components: 1) principles, 2) objectives, 3) processes, 4) evaluation, 5) essential conditions for implementation, and 6) supporting factors. The quality evaluation.